Correction: Pre- and postdiagnosis growth failure, adult short stature, and untreated growth hormone deficiency in radiotherapy-treated long-term survivors of childhood brain tumor. - Julia Anttonen; Tiina Remes; Pekka Arikoski; Päivi Lähteenmäki; Mikko Arola; Arja Harila-Saari; Tuula Lönnqvist; Tytti Pokka; Pekka Riikonen; Kirsti Sirkiä; Heikki Rantala; Marja Ojaniemi (PLoS ONE, 2023)
[This corrects the article DOI: 10.1371/journal.pone.0274274.].